Enzymatic fingerprinting reveals specific xyloglucan and pectin signatures in the cell wall purified with primary plasmodesmata - Paterlini, A.; Sechet, J.; Immel, F.; Grison, M. S.; Pilard, S.; Pelloux, J.; Mouille, G.; Bayer, E. M.; Voxeur, A. (Frontiers in Plant Science, 2022)
Plasmodesmata (PD) pores connect neighbouring plant cells and enable direct transport across the cell wall. Understanding the molecular composition of these structures is essential to address their formation and later dynamic regulation. Here we provide a biochemical characterisation of the cell wall co-purified with primary PD of Arabidopsis thaliana cell cultures. To achieve this result we combined subcellular fractionation, polysaccharide analyses and enzymatic fingerprinting approaches. Relative to the rest of the cell wall, specific patterns were observed in the PD fraction. Most xyloglucans, although possibly not abundant as a group, were fucosylated. Homogalacturonans displayed short methylated stretches while rhamnogalacturonan I species were remarkably abundant. Full rhamnogalacturonan II forms, highly methyl-acetylated, were also present. We additionally showed that these domains, compared to the broad wall, are less affected by wall modifying activities during a time interval of days. Overall, the protocol and the data presented here open new opportunities for the study of wall polysaccharides associated with PD.